2018
DOI: 10.1093/brain/awy101
|View full text |Cite|
|
Sign up to set email alerts
|

Retraining speech production and fluency in non-fluent/agrammatic primary progressive aphasia

Abstract: The non-fluent/agrammatic variant of primary progressive aphasia (nfvPPA) presents with a gradual decline in grammar and motor speech resulting from selective degeneration of speech-language regions in the brain. There has been considerable progress in identifying treatment approaches to remediate language deficits in other primary progressive aphasia variants; however, interventions for the core deficits in nfvPPA have yet to be systematically investigated. Further, the neural mechanisms that support behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 98 publications
5
78
2
1
Order By: Relevance
“…This result may seem surprising in nfvPPA, which is partially defined by nonfluency. The sustained ability of nonfluent patients with left frontal damage to mimic fluent speech stimuli, however, is sufficiently well established to be the basis of therapeutic trials in nfvPPA. In addition, contrary to some prior research on bvFTD, we found no diagnostic group differences in standard deviation of fundamental frequency.…”
Section: Discussioncontrasting
confidence: 98%
“…This result may seem surprising in nfvPPA, which is partially defined by nonfluency. The sustained ability of nonfluent patients with left frontal damage to mimic fluent speech stimuli, however, is sufficiently well established to be the basis of therapeutic trials in nfvPPA. In addition, contrary to some prior research on bvFTD, we found no diagnostic group differences in standard deviation of fundamental frequency.…”
Section: Discussioncontrasting
confidence: 98%
“…Although in our nfvPPA sample we did not find significant tau deposition in other regions of the brain connected with the anterior node of the syntactic network, such as the supplementary motor area or anterior cingulate area, which is connected to the anterior node through the aslant tract (37), these other regions could show abnormal deposition with lower thresholds or in other samples. In nfvPPA, another group has found increased tau deposition in the supplementary motor area, but the sample showed heterogeneous findings (42), which suggests that this unusual and still poorly understood syndrome may have various underlying neuroanatomic substrates loading differently in different patient samples.…”
Section: Discussioncontrasting
confidence: 84%
“…Because the disease begins with impairment of functions such as verbal fluency ( Fig. 2A), mediated by the anterior node, it is logical to postulate that the anterior node is the epicenter of damage (37,38) and that tau buildup starts there. Clinically detectable impairment, as we found in our patients, begins when anterior node neurons become dysfunctional or die.…”
Section: Discussionmentioning
confidence: 99%
“…6 Sebastian et al 31 found that rates of decline in oral naming were more precipitous in nfaPPA than other variants in part because of apraxia of speech. Education about apraxia of speech, highlighting that speech production is no longer a reliable means of communication despite spared ability to formulate communicative intentions and understand others, may facilitate insight regarding needed therapy and supports, such as structured oral reading, 32 script training with speech entrainment, 33 phonological and orthographic speech and language treatment, 34 and implementation of personalized communication aids and assistive devices/apps. 35 In this case, helping Ms. B's The ethical dilemma in this case arises because Mr. C's wife was concerned about Mr. C's safety when traveling to therapy appointments (nonmaleficence principle) while simultaneously wanting to support his desire to participate in therapy (autonomy principle).…”
Section: The Role Of Patient and Family Education In Planning For Thementioning
confidence: 99%